Evaluation of enzyme-modified wheat gluten as a component of milk replacers for calves - H. Terui; J.L Morrill; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1994)
Holstein bull calves (n=120) were assigned randomly to be fed either of five milk replacers (MR) that contained different amounts of crude protein (CP) and protein from wheat gluten (WG) for 6 weeks. Weight gains of calves fed MR containing 20% CP, with either 0, 30, or 50% of the protein coming from WG, were similar, as were gains of calves fed MR containing 18% CP with either none or 33% of the protein from WG. When WG supplied 33% of the protein, calves fed 18% CP gained as much as calves fed MR containing 20% CP. Calves fed MR containing 20% CP consumed more dry feed than those fed MR containing 18% CP, when both used only milk sources for protein. Calf feces were more solid when calves were fed MR containing 20% CP if 30% of the protein was supplied by WG, compared to when 50% was supplied by WG. Enzymemodified WG was an effective substitute for milk protein in a calf milk replacer.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Wheat gluten; Milk replacers; Calves; Crude protein